THE ROLE OF ENGLISH AS A GLOBAL LANGUAGE - Eminova Diyora Anvarovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores the critical role of language—particularly English—in shaping global communication, cultural exchange, and socio-economic development in the modern “global village.” It discusses how English has attained global prominence through its widespread use as both an official and second language in over 70 countries, often serving as a bridge across diverse linguistic and cultural boundaries. Tracing the historical rise of English from its Anglo-Saxon roots to its current status as a global lingua franca.The piece underscores the need for a balanced and inclusive approach to language policy, advocating for the preservation of linguistic diversity while recognizing the practical benefits of a shared global language.